PENGARUH SARANA PRASARANA DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN PADA SPPBE PT. KARYA USAHA LESTARI - Muhammad Idham Nova Firmansyah; Rike Kusuma Wardhani; Angga Permana Mahaputra (Triwikrama: Jurnal Ilmu Sosial, 2023)
This research aims to determine the simultaneous and partial influence of infrastructure and non-physical work environment on employee performance. This type of research uses quantitative research because it leads to measurement methods and samples to test variables and hypotheses. The data sources in this research use primary and secondary data. The sample in the research consisted of 32 employees at SPPBE PT. Karya Usaha Lestari uses a saturated sampling technique which uses all members of the population as samples. The analysis techniques used are validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, t test, F test, multiple linear regression analysis, and coefficient of determination (R2) test using the SPSS version 25 program. The results of the research show that the results of the t test for the variable Facilities and Infrastructure (X1) have a partially significant effect on employee performance by getting a sig value. 0.002 < 0.05 and the non-physical work environment variable (X2) has a partially significant effect on employee performance with a sig. 0.003 < 0.05. Meanwhile, the results of the F test show that infrastructure (X1) and non-physical work environment (X2) have a significant simultaneous effect on employee performance at SPPBE PT. Karya Usaha Lestari with a value of sig. 0.012 < 0.05. In this research it is also known that the coefficient of determination (R2) Adjusted R square of the non-physical Facilities and Work Environment variables has an influence of 64.5% in influencing employee performance, while the remaining 35.5% is influenced by other variables not discussed in the research This.